Analysis of Organizational Commitment and Competence on Employee Performance at Bank BRI Rantauprapat Branch - Marliana Tambak; Siti Lama’ah Nasution; Christine Herawati Limbong (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect oforganizational commitment and competence to the performance of employees of Bank BRI Rantauprapat Branch. The population in this study were 45 people. The sampling technique used was saturated sampling, so the sample size in this study was 45 people. The data collection method used a questionnaire/questionnaire. The results of multiple linear regression analysis obtained the equation Y = 5.905 + 0.765X1 + 0.495X2. In the partial test (t test) the regression coefficient of the organizational commitment variable obtained a t value of 4.614 > t table 2.018 which means that the organizational commitment variable has a positive and significant effect on the employee performance variable with a significant value of 0.000 < 0.05. The regression coefficient for the competency variable obtained the t count value of 2.859 > t table 2, 018 which means that the competence variable has a positive and significant effect on the employee performance variable with a significant value of 0.007 <0.05. The results of the F test obtained the Fcount value of 35.678 > Ftable 3.22 with a significant value of 0.000 <0.05 so it can be concluded that the variables of organizational commitment and competence simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination test showthat variable organizational commitment and competence have an influence of 62.9%on employee performance variables, while the remaining 37.1% is influenced by other variables that are outside this research.